2000
DOI: 10.1034/j.1399-0012.2000.140404.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and opinions about organ donation among urban high school students: pilot test of a health education program

Abstract: Overall, this pilot study provided encouraging evidence that the classroom health education program affected knowledge about organ donation, and that opinions about organ donation are responsive to increases in knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 15 publications
0
56
1
4
Order By: Relevance
“…The first component was adapted from the work of Sander [30] and Weaver [42]. This scale consisted of 16 items that had true/false response options.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first component was adapted from the work of Sander [30] and Weaver [42]. This scale consisted of 16 items that had true/false response options.…”
Section: Methodsmentioning
confidence: 99%
“…It might be that knowing a transplant recipient is an example of consciousness raising, which is one of the ten theorized processes that have received the most empirical support. Several donation-related interventions were developed with the goal of consciousness raising [23,42,70,71]. For example, the Project ACTS: About Choices in Transplantation and Sharing intervention package includes a culturally-sensitive video in which living donors, donor families, and recipients talk candidly about their experience with donation and/or transplantation in order to create a personal connection.…”
Section: Experientialmentioning
confidence: 99%
“…Potential donors' concerns related to the surgical procedure and recovery following live kidney donation may not reflect knowledge about new advances in transplantation (24)(25)(26). confidence intervals (--).…”
Section: Discussionmentioning
confidence: 99%
“…Most such studies emphasise the importance of knowledge on organ donation and transplantation in determining willingness to donate organs (4)(5)(6)(7)(8)(9)(10). On the other hand, many authors have also identified the role of religion in guiding people's viewpoints and attitude toward organ donation (7,, people become more willing to donate when they know that religious leaders (RLs) support organ donation (15).…”
Section: Introductionmentioning
confidence: 99%